A TOEFL TRAINING FOR STUDENTS OF GRADE XII SMAN I MASBAGIK FOR THE PREPARATION OF OVERSEAS SCHOLARSHIP APPLICATIONS - Suherman, Andri; Kertawijaya, Lalu (LPPM Univ. Ibn Khaldun Bogor, 2023)
This community service aims to provide TOEFL training to students of grade XII SMA I Masbagik (East Lombok Regency-West Nusa Tenggara). The knowledge and skills they gained from this TOEFL training can later be used to meet the requirements when applying for overseas scholarship programs. 20 students participated in this TOEFL training which was held three times a week for one month, in December 2022. The results of pre-test and post-test indicated that each participant showed an increase in their TOEFL score after the training. In addition, the data gained from interview process revealed the participants’ perceptions which reported positive responses to this TOEFL training. The implication of this community service is that we acknowledge what difficulties students of grade XII have experienced in learning TOEFL and solutions that can be done to help them. Despite this, the limitation of this TOEFL training is that it only involves relatively few participants and in a relatively short amount of time. The next TOEFL training can recruit more participants and allocate a longer training time to obtain maximum result.